The Influence of Young Entrepreneur School (YES) Training Model on Knowledge, Attitude and Employee Skills Competence - Trisetiyanto, Adi Nova; Syamwil, Rodia; Widjanarko, Dwi (Universitas Negeri Semarang, 2019)
Vocational High School (SMK) be expected to decrease the number of unemployment in Indonesia, not only as a job seeker but also as a job field creator (entrepreneur). The aims of the research are to produce a model of entrepreneurship training and to examine increasing of entrepreneur competence of Vocational High School students after using the model. The study used research and development (R & D) method, with four steps (1) defining and designing models; (2) doing validation by an expert; (3) doing a limited trial; (4) examining influence of model and getting final result of model. The results of research shown that the model of the Young Entrepreneur School (YES) training which is contained of Problem Base Learning elements, Vocational Education Concept, Associate by Technical Assistance and Knowledge, skills and attitudes assessment. Increased knowledge competence by 12%, attitude competence 60% and skill competency 58%. The important of finding model in training model of electronic services, where the students practiced the technical and management of entrepreneur. The benefit of this research in science and society was being a reference in giving entrepreneur training for students of Vocational High School. Thought this research was expected that could be reduce the number of unemployment for graduating of Vocational High School.